Monetary policy between stability and growth - Nikola Fabris (Journal of Central Banking Theory and Practice, 2024)
The global financial crisis and the coronavirus pandemic were marked by expansionary policies of key central banks in an attempt to stop the recession. The degree of expansiveness of monetary policy was unprecedented. As a result of expansionary policies, global inflation has been present since 2021. The change in the macroeconomic environment has led to a turnaround in monetary policy pursuits and a rapid rise in reference interest rates. The FED reacted much faster than the ECB and that is why inflation was lower in the USA compared to the euro area. All announcements for 2023 point to the continuation of contractionary policies. The subject of the paper's analysis is the monetary policy of key central banks, as well as expectations for the next period. The paper raises the question of whether central banks have gone from one extreme of overly expansionary monetary policy to the other extreme of overly contractionary monetary policy and whether such policies carry the risk of reoccurrence of recession. The paper also contains recommendations for improving existing monetary policy regimes, as well as for creating a completely new monetary policy regime which will be based on two nominal anchors.
Keywords: E50; E52; E58; 330; Monetary Policy; FED; ECB; Inflation; Two Nominal Anchors